2012
DOI: 10.1021/jm300031j
|View full text |Cite
|
Sign up to set email alerts
|

Dithiocarbamates Strongly Inhibit Carbonic Anhydrases and Show Antiglaucoma Action in Vivo

Abstract: A series of dithiocarbamates was prepared by reaction of primary/secondary amines with carbon disulfide in the presence of bases. These compounds were tested for the inhibition of 4 human (h) isoforms of the zinc enzyme carbonic anhydrase, CA (EC 4.2.1.1), hCA I, II, IX and XII, involved in pathologies such as glaucoma (CA II and XII) or cancer (CA IX). Several low nanomolar inhibitors targeting these CAs were detected. X-ray crystal structure of hCA II adduct with morpholine dithiocarbamate evidenced the inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
145
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 219 publications
(150 citation statements)
references
References 85 publications
3
145
0
2
Order By: Relevance
“…The x-ray crystal structures were also reported for three DTCs complexed to hCA II, compounds 28-30 ( Figure 5). DTCs 28-30 inhibited hCA II with K I s of 25, 41 and 0.95 nM, respectively, and hCA IX with K I s of 53, 757 and 6.2 nM, respectively 66 . As seen from Figure 5, the binding mode of the ZBG present in 29 is identical to that of trithiocarbonate (with one sulphur coordinated to the metal ion), but the organic scaffold present in the DTC was observed to make extensive contacts with many amino acid residues from the active site, which explains the wide range of inhibitory power of these derivatives (from the subnanomolar to the micromolar, for the entire series of around 30 DTC reported thus far 59,66 ).…”
Section: Journal Of Enzyme Inhibition and Medicinal Chemistrymentioning
confidence: 93%
See 3 more Smart Citations
“…The x-ray crystal structures were also reported for three DTCs complexed to hCA II, compounds 28-30 ( Figure 5). DTCs 28-30 inhibited hCA II with K I s of 25, 41 and 0.95 nM, respectively, and hCA IX with K I s of 53, 757 and 6.2 nM, respectively 66 . As seen from Figure 5, the binding mode of the ZBG present in 29 is identical to that of trithiocarbonate (with one sulphur coordinated to the metal ion), but the organic scaffold present in the DTC was observed to make extensive contacts with many amino acid residues from the active site, which explains the wide range of inhibitory power of these derivatives (from the subnanomolar to the micromolar, for the entire series of around 30 DTC reported thus far 59,66 ).…”
Section: Journal Of Enzyme Inhibition and Medicinal Chemistrymentioning
confidence: 93%
“…DTCs 28-30 inhibited hCA II with K I s of 25, 41 and 0.95 nM, respectively, and hCA IX with K I s of 53, 757 and 6.2 nM, respectively 66 . As seen from Figure 5, the binding mode of the ZBG present in 29 is identical to that of trithiocarbonate (with one sulphur coordinated to the metal ion), but the organic scaffold present in the DTC was observed to make extensive contacts with many amino acid residues from the active site, which explains the wide range of inhibitory power of these derivatives (from the subnanomolar to the micromolar, for the entire series of around 30 DTC reported thus far 59,66 ). Interestingly, the highly water-soluble DTC 30 was also effective in vivo as an anti-glaucoma agent when administered topically directly to the eye of hypertensive rabbits 66 , a widely used animal model of glaucoma 39 .…”
Section: Journal Of Enzyme Inhibition and Medicinal Chemistrymentioning
confidence: 93%
See 2 more Smart Citations
“…Dithiocarbamates (DTCs) were discovered as a completely new class of CAIs only recently, after the investigation of some inorganic anions acting in this way [45][46][47][48][49][50]. Indeed, the simple inorganic compound trithiocarbonate (TTC, CS 3 2-), [51] for which an X-ray crystal structure in complex with the isoform hCA II was available, showed that the inhibitor is bound to the Zn(II) ion from the enzyme catalytic site through one of its three equivalent sulfur atoms, whereas a second such atom interacted with the conserved Thr199 amino acid residue.…”
Section: Dithiocarbamatesmentioning
confidence: 99%